2006
DOI: 10.1152/ajpheart.01363.2005
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of PKC-ζ in normal and angiotensin II-accelerated neointimal growth after vascular injury

Abstract: The contribution of atypical protein kinase C (PKC)-zeta to ANG II-accelerated restenosis after endoluminal vascular injury was investigated by using the rat carotid balloon injury model. Exposure of injured arteries to ANG II resulted in an extensive neointimal thickening (1.9 times) compared with vehicle at day 14. Treatment with PKC-zeta antisense, but not scrambled, oligonucleotides reduced neointimal formation observed in the presence or absence of ANG II. Examination of early events (2 days) after injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Consistent with the notion that PKC is a novel G␣ q effector, agonists acting through G q -coupled GPCR such as angiotensin II, phenylephrine, platelet-activating-factor, or thromboxane A2 have been shown to promote PKC translocation and activation in several cell types (24 -26, 32, 33), and PKC has been suggested to participate in GPCR-mediated control of cell proliferation (25)(26)(27), eosinophil degranulation (32), or smooth muscle cell adhesion, spreading, and hypertrophy (25). Several authors have suggested a role for PKC in ERK1/2 activation by GPCR (34,35), although another recent report indicates that inhibition of PKC in adult cardiomyocytes has no effect in ERK1/2 activation by G q -coupled GPCR (36).…”
Section: Discussionmentioning
confidence: 83%
“…Consistent with the notion that PKC is a novel G␣ q effector, agonists acting through G q -coupled GPCR such as angiotensin II, phenylephrine, platelet-activating-factor, or thromboxane A2 have been shown to promote PKC translocation and activation in several cell types (24 -26, 32, 33), and PKC has been suggested to participate in GPCR-mediated control of cell proliferation (25)(26)(27), eosinophil degranulation (32), or smooth muscle cell adhesion, spreading, and hypertrophy (25). Several authors have suggested a role for PKC in ERK1/2 activation by GPCR (34,35), although another recent report indicates that inhibition of PKC in adult cardiomyocytes has no effect in ERK1/2 activation by G q -coupled GPCR (36).…”
Section: Discussionmentioning
confidence: 83%
“…Inhibition of protein kinase C-attenuated medial cellularity and expression of inflammatory mediators. 29 ACE inhibitors have been shown to inhibit neointima formation in response to vascular injury in several models and species, such as in balloon-induced vascular injury in rats 30 and guinea pig, 31 in allograft-induced intima formation in rats, 32 and cuff-induced neointima formation in mice. 24,33 Several follow-up studies in these models showed that the favorable effects of ACE inhibition could be attributed, in part, to the bradykinin/endothelial NO synthase pathway and/or oxidative stress/NAD(P)H pathway.…”
Section: Ace and Neointimal Thickening/restenosismentioning
confidence: 99%
“…1,2 Angiotensin (Ang) II is known to induce oxidative stress and leukocyte adhesion in the vascular wall, 3,4 whereas the local renin-angiotensin system in the vasculature plays an important role in the development of injury-induced inflammation. 5,6 Recent studies suggest an efficacy of Ang II type 1 receptor blocker (ARB) in reducing intimal hyperplasia after mechanical injury in animal models. 7,8 However, the role of ARB in the modulation of vascular inflammation at the early phase of the injury has not been fully investigated.…”
mentioning
confidence: 99%